1984
DOI: 10.1111/j.1476-5381.1984.tb10766.x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of cat tracheobronchial and pulmonary arterial smooth muscle by vasoactive intestinal peptide: lack of influence by peptidase inhibitors

Abstract: 1Vasoactive intestinal peptide (VIP) caused concentration-dependent relaxation in precontracted segments of trachea, hilar bronchus, intrapulmonary bronchus and intrapulmonary artery (IPA) isolated from cat lungs. 2 VIP-induced relaxation responses were abolished by preincubation of tissues with the proteolytic enzyme, a-chymotrypsin (2 units ml-). At the concentration employed, a-chymotrypsin treatment did not adversely affect tissue viability as isoprenaline and bethanechol continued to relax airways and IPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 21 publications
4
11
0
Order By: Relevance
“…However, it is unlikely that an opioid peptide is involved, since the NANC response is unaffected by naloxone (Ellis & Farmer, 1989). Our results agree with those obtained with cat trachea (Altiere & Diamond, 1984), in that, in guinea-pig trachea, enzymatic inactivation of VIP does not seem to be an important mechanism. If VIP or PHI do play a role as NANC transmitters in the lung, they may be removed by the circulation and metabolized by blood-borne peptidases.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…However, it is unlikely that an opioid peptide is involved, since the NANC response is unaffected by naloxone (Ellis & Farmer, 1989). Our results agree with those obtained with cat trachea (Altiere & Diamond, 1984), in that, in guinea-pig trachea, enzymatic inactivation of VIP does not seem to be an important mechanism. If VIP or PHI do play a role as NANC transmitters in the lung, they may be removed by the circulation and metabolized by blood-borne peptidases.…”
Section: Resultssupporting
confidence: 82%
“…Effects of a-chymotrypsin were prevented completely by preincubation with aprotinin (1.75umlP1; Figures 2 and 3). In the presence of occhymotrypsin, responses to both VIP and PHI, even achea, whereas responses to VIP are abol--chymotrypsin (Altiere & Diamond, 1984), " inhibitory response is unaffected (Altiere id, 1985). This suggested firstly, that VIP, (Matsuzaki et al, 1980;Ellis & Farmer, 1989).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The substantial remainder of α-chymotrypsin-and VIP-antagonist-resistant and L-NAME-insensitive NANC relaxation was suppressed by tetrodotoxin. Furthermore, the overall conclusion of earlier works concerning the effects of α-chymotrypsin on exogenously applied VIP or NANC relaxation, seems to be that VIP is not involved in the NANC relaxation [22]. These observations may also indicate that neurotransmitters other than VIP and NO are involved in the NANC inhibitory neurotransmission in the airway.…”
Section: Discussionsupporting
confidence: 48%
“…Further, in feline airways in vitro aprotinin Lions with intact epithelium, but had no and captopril have no effect on VIP-induced relaxation achea ( Figure 6). The pD2 value for intact (Altiere & Diamond, 1984). Previous studies in our laboratory nce of thiorphan, was 8.07 + 0.10 and this also showed that aprotinin had no effect on responses of rom the value of 8.30 + 0.08 in denuded guinea-pig trachea, either to exogenous VIP or to NANC ro2.3, n = 7).…”
Section: Effects Ofpeptidase Inhibitorssupporting
confidence: 57%